2002
DOI: 10.1080/00224540209603920
|View full text |Cite
|
Sign up to set email alerts
|

Racial Bias in Decisions Made by Mock Jurors Evaluating a Case of Sexual Harassment

Abstract: White (N = 161) and Black (N = 152) college students served as mock jurors in a simulated civil case in which a female plaintiff accused a male defendant of sexual harassment. The authors experimentally manipulated the race (Black or White) of the litigants and asked the mock jurors to decide whether the defendant was guilty; to rate the certainty of their belief in the defendant's guilt; and, when they judged the defendant guilty, to recommend an award to the plaintiff. Mock jurors of both races tended to fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 18 publications
3
35
3
Order By: Relevance
“…Further research has seen similar support for the similarity-leniency hypothesis in race-salient and non-race-salient trials, such that Black jurors rated Black defendants as less aggressive and less likely to be guilty than did White jurors (Abwender & Hough, 2001;Sommors & Ellsworth, 2000;Wuensch, Campbell, Kesler, & Moore, 2002). These findings suggest jurors in hate crime trials may also be more lenient toward defendants they consider to be similar to themselves.…”
Section: Ingroup/outgroup Theory and Assignment Of Punishmentsupporting
confidence: 49%
See 2 more Smart Citations
“…Further research has seen similar support for the similarity-leniency hypothesis in race-salient and non-race-salient trials, such that Black jurors rated Black defendants as less aggressive and less likely to be guilty than did White jurors (Abwender & Hough, 2001;Sommors & Ellsworth, 2000;Wuensch, Campbell, Kesler, & Moore, 2002). These findings suggest jurors in hate crime trials may also be more lenient toward defendants they consider to be similar to themselves.…”
Section: Ingroup/outgroup Theory and Assignment Of Punishmentsupporting
confidence: 49%
“…In the current context, it is important to examine ingroup/outgroup theories as they can play a critical role in jury decision-making, particularly when examining how jurors may categorize the defendants or victims involved in a trial (Taylor & Hosch, 2004). Two predominant theories have emerged that attempt to explain how these ingroup/outgroup mechanisms apply in the context of jury decision-making: (1) similarity-leniency hypothesis and Many juror decision-making studies have looked at the first of these theories, similarityleniency hypothesis, which proposes that jurors are more lenient toward defendants who are similar to themselves, rather than dissimilar (Abwender & Hough, 2001;Kerr, Hymes, Anderson, & Weathers, 1995;Sommors & Ellsworth, 2000;Van Proojien, 2006;Wuensch, Campbell, Kesler, & Moore, 2002). Kerr and colleagues (1995) found that when there was not overwhelming evidence of a defendant"s guilt, mock jurors were more lenient toward defendants who practiced the same religion, as compared to defendants who practiced another religion.…”
Section: Ingroup/outgroup Theory and Assignment Of Punishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature suggests that an individual's race and gender may influence their evaluations of criminals and their behaviors, particularly with regard to sentencing (Dane and Wrightsman 1982;Egbert et al 1992;Moore et al 1994;Wuensch et al 2002). In addition, how serious an individual believes a crime to be affects several of their reactions to that crime 14 In order to be deemed significant, a factor had to have an eigenvalue greater than one and explain more than 20 percent of the variance.…”
Section: Control Variablesmentioning
confidence: 99%
“…However, shallow rates of discounting might also represent a greater willingness for the African American recipient to experience the full outcome. Future research will be needed to parse these possibilities, but the existing literature (see Hughes & Tuch, 2003;Murrell et al, 1994;Wuensch, Campbell, Kesler, & Moore, 2002) would suggest that the last of them is perhaps the most likely explanation.…”
Section: Discussionmentioning
confidence: 99%